Traumatic brain injury in pediatric population - Which social inclusion? - Afonso, Carla; Interna de MFR do Centro de Medicina de Reabilitação de Alcoitão, Portugal (2013)
IntroductionTraumatic brain injuries (TBI) are a very important cause of children morbidity and disability, with a negativeimpact on their life quality. Outcomes vary with the severity of injury, child age at injury, premorbid child characteristics, family factors and the families' socioeconomic status.AimTo evaluate the social inclusion of children following a traumatic brain injury after hospital discharge.Patients and MethodsThe authors made a retrospective study of the inpatients of a specific unit of the Pediatric Development andRehabilitation Service, dedicated to the care of children that, at admission, were in coma or in a minimalresponsive state. Medical records were reviewed corresponding to children admitted to this unit between 1996and 2007 and their social inclusion was evaluated.ConclusionChildren following traumatic brain injuries face serious difficulties when they return to their familiar environmentin terms of skills, behaviour, communication and education. They could also be a physical, emotional and financialburden to their families and society. Prevention measures and oriented rehabilitation programs are essential toassure a better outcome for children with TBI.